Onset of foreland basin deposition in the Neuquén Basin (34°-35°S): New data from sedimentary petrology and U–Pb dating of detrital zircons from the Upper Cretaceous non-marine deposits - Gómez, Ricardo (2019)
Fil: Gómez, Ricardo. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro, Argentina.